Influence of cellulose fiber content on morphology and properties of poly(Lactic acid)/propylene-ethylene copolymer/cellulose composites - Wacharawichanant, Sirirat; Opasakornwong, Patteera; Poohoi, Ratchadakorn; Phankokkruad, Manop (My University, 2021)
This work studied the effects of medium-length fibrous cellulose (MFC) on the morphology, mechanical and thermal properties of poly(lactic acid) (PLA)/propylene-ethylene copolymer (PEC) (90/10) blends. The morphological analysis of PLA/MFC composites observed MFC fibers inserted in the PLA matrix and MFC appeared agglomeration when added high MFC loading. The phase morphology showed the two-phase separation of PLA/PEC blends. The presence of PEC reduced the agglomeration of MFC fibers in polymer matrix. The tensile stress and strain curves found that the ultimate stress of PLA was the highest value and the addition of MFC increased Young’s modulus of PLA/MFC and PLA/PEC/MFC composites. The PEC presence improved the strain at breaking point of PLA/PEC blends. The thermal properties found that the incorporation of MFC did not improve the thermal stability of PLA/MFC and PLA/PEC/MFC composites due to the PLA had degradation temperature higher than MFC.
Keywords: Cellulose; Mechanical properties; Poly(lactic acid); Propylene-ethylene copolymer